Turkish textile and clothing SMEs: Importance of organizational learning, digitalization, and internationalization - Divrik, Bahar; Baykal, Elif (My University, 2024)
The Turkish textile and clothing (TTC) industries, which are mainly made of small and medium enterprises (SMEs), are the main source of export for the Turkish economy since the end of 1980s. The introduction of digital technologies has changed the competition for the TTC industries and this change has been accelerated after the covid-19 pandemic. Digitalization of SMEs is accepted as a social and technical process in which organizational learning is the main actor and therefore, the aim of this research is to explore the relation between organizational learning, digitalization, and internationalization for TTC industries. A parallel-results convergent mixed method approach in which qualitative and quantitave analysis are performed seperately and integrated later is applied in this research. The data of the research were collected by semi-structured interviews and survey questionnaires, which are analyzed in MAXQDA and analysis of moment structures.
Keywords: Digitalization; Internationalization; Organizational Learning; Small And Medium Enterprises; Turkish Textile And Clothing Industries